Structural monitoring and remaining fatigue life estimation of typical welded crack details in the Manhattan Bridge. (15th March 2021) - Tochaei, Emad Norouzzadeh; Fang, Zheng; Taylor, Todd; Babanajad, Saeed; Ansari, Farhad
Highlights: Investigated evolution of damage in welded connection details of the iconic Manhattan Bridge. Instrumented the bridge for remote real-time monitoring of the key cracked welded connections. Sensor data revealed cyclic axle loads of the transit trains as the source for damage. Evaluated the remaining fatigue life of the typical cracks by LEFM employing both deterministic and probabilistic methods. Abstract: Manhattan Bridge is a suspension structure that connects Manhattan to Downtown Brooklyn. This bridge is over 110 years old and subjected to daily repeated axles of transit trains and other vehicular traffic. Visual inspections of the bridge revealed manifestation of many cracks in the welded details due to the out-of-plane forces at the connections between transit and floor beams. The research reported herein, pertains to the fatigue life evaluation and reliability assessment of typical cracked welded details. The bridge was instrumented with a real-time structural health monitoring system based on FBG sensors for remote monitoring of the cracked connections. Both deterministic and probabilistic approaches were employed for prediction of the remaining fatigue life of typical cracked details. For the same fatigue reliability index of 2.3, the deterministic and probability based methods yielded remaining fatigue life of 369 and 120 years, respectively, for the typical welded connections details of the bridge.